ANALYSIS OF MECHANICAL COMPETENCY AND SERVICE PRICES ON CUSTOMER SATISFACTION AT CV. NIRMALA KN AUTOCARE WORKS - Shidqi, Fahmi Shidqi; Supriyatna, Deddy (Department of Mechanical Engineering Education, 2023)
High-intensity use of personal transportation equipment will result in damages, which will disrupt daily performance; therefore, vehicle maintenance and repairs need to be carried out regularly and periodically. The problem that often occurs is that service prices are expensive, and yet the results are unsatisfactory. The reason behind this can be inadequate mechanical skills or competence. This research tested the relationship between mechanical competence and service prices on customer satisfaction at CV. Karya Nirmala Auto Care Jl. Pandeglang-Rangkas Gang H Kabal, Kabayan, Pandeglang Regency, Banten. This research uses quantitative methods, service price data, and mechanic competency at the Karya Nirmala Auto Care workshop. Data was collected using interviews and questionnaires. The data analysis used was multiple correlation, and the results showed a strong relationship between mechanical competence and service prices on customer satisfaction.